A point prevalence study of 150 patients with idiopathic retinal vasculitis: 2. Clinical relevance of antiretinal autoimmunity and circulating immune complexes. Issue 9 (September 1989) - Kasp, E; Graham, E M; Stanford, M R; Sanders, M D; Dumonde, D C
Abstract : This study describes the occurrence of antiretinal antibodies and circulating immune complexes in the sera of a large series of patients with idiopathic retinal vasculitis whose ophthalmological and clinical features are presented in Part 1. Antiretinal antibodies were measured by indirect immunofluorescence and passive haemagglutination, and circulating immune complexes were measured by polyethylene glycol precipitation and Clq binding. The occurrence of antiretinal antibodies and that of circulating immune complexes were analysed in relation to each other, to severity of retinal disease, to the type of associated systemic inflammatory disease, and to the presence of individual features of retinal inflammation. In patients with retinal vasculitis together with systemic inflammatory disease circulating immune complexes were usually accompanied by antiretinal antibodies. However, those patients with antiretinal antibodies in the absence of circulating immune complexes tended to have more severe retinal vasculitis, a feature particularly evident in Behçet's disease (p = 0.028). In patients with isolated retinal vasculitis, severity of disease was associated with antiretinal antibody (p = 0.013), as well as with the occurrence of both antiretinal antibody and circulating immune complexes together (p = 0.010). In the series as a whole there was a tendency for individual features of retinal vasculitis to be associated with antiretinal antibodies unaccompanied by circulating immune complexes; especially in macular oedema (p = 0.028). In isolated retinal vasculitis there was also an additive effect of antiretinal antibodies and circulating immune complexes in relation to disease severity; in contrast, in patients with systemic inflammatory disease, the coexistence of antiretinal antibodies and concluded that both antiretinal autoimmunity and circulating immune complexes may act as immunopathogenetic factors in idiopathic retinal vasculitis but that, in certain patients, circulating immune complex formation seems to protect against the more severe forms of autoimmune retinal inflammatory disease.